KEGUNAAN PENDEKATAN FENOMENOLOGI DALAM KAJIAN AGAMA - Dalinur M. Nur (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
In everyday life, people move on the world that has been covered with interpretations and categories of science and philosophy. Interpretations are often colored by the interests, life situations and habits, so people have forgotten what their world, the pure life, where all forms of interpretation placed. The dominance of positivism paradigm for many years on the world of science, not only in natural sciences but also in the social sciences and even humanities sciences, which have resulted crisis of science. The problem is not the application of positivistic mindset towards the natural sciences, because it is consistent, but positivism in the social sciences, the society and human beings as historical beings. Problematic positivism in the social sciences, which eliminates the role of the subject in the form a 'social fact', has prompted the emergence of an effort to find a new base and methodological support for the social sciences to 'restore' the role of the subject into the process of science itself. One such approach is phenomenological approach that is briefly discussed below. In this paper, the writer focuses on the discussion of definition of phenomenology, methods of phenomenology in religious studies, phenomenological methodology in the qualitative approach, and then how the phenomenological approach.